This will be interesting : a novel - Asher, E. B. (Avon, 2026)
"A stand-alone set in the same magical, madcap world as E. B. Asher's USA Today bestseller This Will Be Fun, a heartwarming, hilarious fantasy about a group of questmates turned friends-or maybe more-who must get to the bottom of an assassination plot gone wrong"-- Provided by publisher.